2018
DOI: 10.3345/kjp.2018.07227
|View full text |Cite
|
Sign up to set email alerts
|

The adiposity rebound in the 21st century children: meaning for what?

Abstract: With the increase in the prevalence of overweight and obesity worldwide, early adiposity rebound, which is known to have a strong association with obesity, has recently been a focus of research. Early adiposity rebound is conventionally known to have a close relationship with non-communicable diseases. However, novel insights into early adiposity rebound have implied an acceleration of growth and puberty, which is directly reflected in the trends in the timing of adiposity rebound, in the 21st century compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 55 publications
1
46
0
2
Order By: Relevance
“…Botton et al reported that regardless of birth weight, rapid weight gain even in the first 6 months is associated with obesity [30]. Breastfeeding, the only factor known to have protective effect against obesity [11], showed negative correlation with early weight gain during the first 11 months in our study. Therefore, the benefits of breastfeeding in LBW and VLBW infants cannot be overestimated [8].…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Botton et al reported that regardless of birth weight, rapid weight gain even in the first 6 months is associated with obesity [30]. Breastfeeding, the only factor known to have protective effect against obesity [11], showed negative correlation with early weight gain during the first 11 months in our study. Therefore, the benefits of breastfeeding in LBW and VLBW infants cannot be overestimated [8].…”
Section: Discussionsupporting
confidence: 56%
“…The timing of AR in the Korean growth standards, which was developed using crosssectional data from the National Anthropometric Survey in 1997 and 2005 [16], was estimated as 5.5 years (66 months) in both sexes [11]. Considering that we had insufficient frequency of measured data in this study, the median timing of AR would be between 3.8 years (Exam-V) and 4.8 years (Exam-VI) of age, regardless of birth weight and sex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high BMI at age 5 years are also known as an important predictor to later obesity [ 13 ]. Therefore, we analyzed the BMI status at 57 months of age (Exam-VI) and classified as follows: underweight, BMI < 5 th percentile; normal weight, 5 th percentile ≤ BMI < 85 th percentile; overweight, 85 th percentile ≤ BMI < 95 th percentile; and obesity, BMI ≥ 95 th percentile.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, higher risk of obesity of rapid grower is not confined only to preterm or small for gestational age infants, although rapid weight gain is most likely to occur in LBW infants. Like secular changes in body size and tempo of growth have occurred in most countries, the timing of AR has shifted by better nutrition, hygiene, and health status [ 13 ]. This shifting of AR timing was observed not only in children with overweight and obesity, but also in children with low BMI [ 14 ].…”
Section: Introductionmentioning
confidence: 99%